Close approach of a cloud of particles around an oblate planet - Gomes, Vivian M. [UNESP]; Oliveira, Geraldo M. C.; Prado, Antonio F. B. A.; Sanchez, Diogo M. (My University, 2016)
The goal of the present paper is to study close approaches of a cloud of particles with an oblate planet, which means that there is a J2 term in the gravitational potential of the planet. This cloud of particles is assumed to be created during the passage of a spacecraft by the periapsis of its orbit, by an explosion or any other disruptive event. The system is formed by two large bodies (Sun and planet), assumed to be in circular orbits around the center of mass of the system, and the cloud of particles. The particles that belong to the cloud make a close approach to the flat planet and then they are dispersed by the gravitational force of the planet. The motion is governed by the equations of motion given by the planar restricted circular three-body problem plus the effects of the oblateness of the planet. Jupiter is used for numerical simulations. The results show the differences between the behavior of the cloud after the passage, considering or not the effects of the oblateness of the planet. The results show that the oblateness of the planet is equivalent to an increase in the mass of the planet.
Keywords: Astrodynamics; Close approaches; Oblate planet; Orbital maneuver